Foot and Ankle Fellowship Faculty Research Productivity. Issue 4 (22nd October 2020) - Khwaja, Ansab M.; Bridge, Nathaniel; Sherman, Nathan; Du, Peter Z.
Category: Other Introduction/Purpose: Academic productivity within orthopaedic subspecialties is important in developing generalizable knowledge, challenging biases, and evolving practice management. Productivity is linked to academic status and can affect compensation. This study evaluated the research activity of faculty at foot and ankle surgery fellowship programs in the United States and associated Canadian programs. The primary objective was to describe the publishing productivity of American Orthopaedic Foot & Ankle Society (AOFAS) fellowship faculty. Methods: Program characteristics from orthopaedic foot and ankle fellowship programs across the United States and Canada were collected from AOFAS and each program's respective websites. The studied faculty characteristics consisted of years in practice, academic rank, extent of training, and gender. Specific program characteristics were recorded, including Accreditation Council for Graduate Medical Education approval, academic affiliation, fellow research requirement, number of fellows, number of associated faculty members. Data analysis of faculty productivity (Publications, number of publications in specific journals, number of citations, and Hirsch index [h index]) was gathered using the Scopus database. Results: A total of 48 AOFAS foot and ankle surgery fellowship programs were identified with an associated 185 faculty members. The mean number of publications per faculty member was 44.9 (sd 53.0; range 0-323) with a mean h-index of 11.9 (sd 10.6; range 0-54). One-hundred and forty-four (77.8%) academic-affiliated faculty had a significantly greater number of publications (p<0.01), total citations (p<0.05), and publications in FAI (p<0.05), JBJS (p<0.05), CORR (p<0.05), and JAAOS (p<0.05) compared to the 41 (22.2%) nonacademic faculty. Nonacademic faculty maintained a h-index of 9.5 (95% CI 7-12), while academic faculty had a h-index of 12.6 (95% CI 11-14), which did not meet statistical significance (p=0.062). There were no significant differences between measures of publication productivity in male and female faculty, except for maximum citations in a single paper (67.1 vs 142.3; p<0.05) Conclusion: Academic-affiliated foot and ankle fellowship faculty have higher research productivity than non-academic surgeons. The mean h-index of foot and ankle fellowship faculty was 11.9, which is lower than that reported in sports, joints, and spine fellowship faculty but higher than that reported for hand fellowship faculty. The analyses presented can aid foot and ankle surgeons in assessing their academic productivity.